The Effectiveness of the Community Learning Service Model Development Through the Literacy Clinic (International Journal of Education and Literature, 2025)
The government has implemented various illiteracy eradication programs at both central and local levels. However, illiteracy remains high, with South Sulawesi ranking sixth nationally. This condition is influenced by the imbalance between the number of Non-Formal Education Units and target areas, limited human resources, as well as learner-related factors such as motivation, age, occupation, distance to learning sites, and monotonous teaching methods. Community learning services through literacy clinics using collaborative methods Reading, Writing Beginning, Structure, Analysis, and Synthesis, combined with project-based learning serve as alternative models to increase community participation and improve learning outcomes. The problem of this research is how the description of the implementation of basic literacy programs through the model "Community Learning Services Through Literacy Clinics"?, and how effective the model "Community Learning Services Through Literacy Clinics with the collaborative method approach?. The purpose of this study was to determine the description of the implementation model of basic literacy education programs and determine the effectiveness of learning outcomes. The results of the study illustrated that the basic literacy program was carried out in collaboration between the resources of the Non-formal Education Unit and the resources in the village/kelurahan government as the organizer and tutor Learning outcomes show that the Community Learning Service Model through the Literacy Clinic with a collaborative method approach was declared effective in improving student learning outcomes.